2002
DOI: 10.3354/meps242119
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the basis of thermotolerance in the reef coral Goniastrea aspera

Abstract: The shallow-water reef coral Goniastrea aspera Verill 1865 has previously been reported to demonstrate differences in within-colony susceptibility to bleaching at elevated sea temperatures; parts of the colony which are exposed to the highest solar radiation are more thermotolerant than areas which are less exposed. In this paper, we show that at elevated experimental sea temperature the 'high light' surfaces lose fewer symbiotic algae, have lower levels of oxidative stress, higher levels of host antioxidant-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
169
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(188 citation statements)
references
References 39 publications
13
169
0
Order By: Relevance
“…Several factors may account for the high level of fungal community dissimilarity found within the pools and the Symbiodinium genotypes. Prior work has shown that physiology of conspecific corals can vary considerably over short distances (Brown et al, 2002a, b;Smith et al, 2007;Bay et al, 2009;Barshis et al, 2010), which could obscure fungal community patterns associated with our measured variables. Furthermore, stochastic recruitment of large numbers of planktonic, benthic or even terrestrial fungi could mask signatures of specialization or obligacy of a small number of taxa.…”
Section: Discussionmentioning
confidence: 88%
“…Several factors may account for the high level of fungal community dissimilarity found within the pools and the Symbiodinium genotypes. Prior work has shown that physiology of conspecific corals can vary considerably over short distances (Brown et al, 2002a, b;Smith et al, 2007;Bay et al, 2009;Barshis et al, 2010), which could obscure fungal community patterns associated with our measured variables. Furthermore, stochastic recruitment of large numbers of planktonic, benthic or even terrestrial fungi could mask signatures of specialization or obligacy of a small number of taxa.…”
Section: Discussionmentioning
confidence: 88%
“…The physical conditions experienced by corals at the study site during low spring tides included elevated temperature, intense solar radiation, sub-aerial exposure and extreme tidal water movements. Temperature and solar radiation effects were maximal during the first two days of Table 4 p values resulting from the Monte Carlo simulations testing for significant differences between diversity indices (Chao1, Alpha and log H 0 ) of microbial communities on different days, within the two coral age groups (*4-and *10-yr-old) sub-aerial exposure, and their negative effects on the physiology of the western sides of colonies have been previously documented in C. aspera at this site (Brown and Dunne 2008;Brown et al 2002). The effects of sub-aerial exposure on increased mucus production have also been highlighted (Jatkar et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…All of the above physical factors have the potential to affect the composition of coral-associated bacteria. High temperatures and solar radiation are known to induce oxidative stress in C. aspera with high levels of oxidative damage and increased antioxidant enzyme levels (CuZn-SOD) being produced under such conditions (Brown et al 2002). It has been suggested that high reactive oxygen concentrations are a barrier to microbial colonization of intracellular sites and that they may also play a role in colonization of micro-organisms at other locations in the coral where active oxygen is produced (Thompson et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Encouragingly, it is becoming evident that some corals demonstrate a degree of thermotolerance (Brown et al 2002;Mydlarz et al 2009) and are capable of survival in acidified conditions (Fine and Tchernov 2007); thus corals may have innate resilience to these aspects of climate change.…”
Section: Introductionmentioning
confidence: 99%